Some New Results on Prime Graphs - Vaidya, Samir K.; Prajapati, Udayan M. (Scientific Research, 2012)
We investigate prime labeling for some graphs resulted by identifying any two vertices of some graphs. We also introduce the concept of strongly prime graph and prove that the graphs Cn, Pn, and K1,n are strongly prime graphs. Moreover we prove that Wn is a strongly prime graph for every even integer n ≥ 4.
Keywords: Prime Labeling; Prime Graph; Strongly Prime Graph